Does Distance Matter in the Age of the Internet? - Mok, Diana; Wellman, Barry; Carrasco, Juan (Urban studies (Edinburgh, Scotland), 2010)
This study is part of the broad debate about the role of distance and technology for interpersonal contact. To the best of the authors' knowledge, this is the first study that systematically and explicitly compares the role of distance in social networks pre- and post-Internet. An analysis is made of the effect of distance on the frequency of e-mail, phone, face-to-face and overall contact in personal networks, and the findings are compared with their pre-Internet counterpart whose data were collected in 1978 in the same East York, Toronto locality. Multilevel models with a spline specification are used to examine the non-linear effects of distance on the frequency of contact. These effects are compared for both very close and somewhat close ties, and for different role relationships: immediate kin, extended kin, friends and neighbours. The results show that e-mail contact is generally insensitive to distance, but tends to increase for transoceanic relationships greater than 3000 miles apart. Face-to-face contact remains strongly related to short distances (within five miles), while distance has little impact on how often people phone each other at the regional level (within 100 miles). The study concludes that e-mail has only somewhat altered the way people maintain their relationships. The frequency of face-to-face contact among socially close friends and relatives has hardly changed between the 1970s and the 2000s, although the frequency of phone contact has slightly increased. Moreover, the sensitivity of these relationships to distance has remained similar, despite the communication opportunities of the Internet and low-cost telephony.